PENGARUH STRATEGI PEMBELAJARAN AKTIF TERHADAP MOTIVASI DAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM SEKOLAH MENENGAH PERTAMA DI SAMARINDA - Hayyi, Abdul; Zurqoni, Zurqoni; Rhendica, Rhendica (Universitas Islam Negeri Alauddin Makassar, 2023)
This research departs from the learning problems of Islamic Religious Education which are caused by low motivation and student learning outcomes. The strategies used include Active Learning. This research aims to determine whether there is an influence of active learning strategies on students’ motivation and learning outcomes. This quantitative research used a survey approach and a comparative causal design. The population were students in grade VIII at SMPN 2 Samarinda, SMPN 9 Samarinda, SMPN 7 Samarinda, and SMPN 14 Samarinda. This research used purposive sampling. The data collection techniques are a questionnaire and documentation, while the data analysis technique is a MANOVA test. The research results show that there is an influence of Active Learning strategies on the motivation and learning outcomes of Islamic Religious Education in Samarinda Middle School. The hypothesis is accepted by using Hotelling's Trace analysis with a strong influence.